2019
DOI: 10.1177/1071181319631451
|View full text |Cite
|
Sign up to set email alerts
|

Updating the Direction Orientation Task: An Aviation Selection Tool

Abstract: Military branches rely on selection and placement testing to help identify individuals who will be well-suited for jobs that they likely have little exposure to or experience with. The goal for this research was to update the Direction Orientation Task (DOT), which is used by both the United States Navy and Air Force as part of their aviation selection batteries. The current version of DOT has limitations such as ceiling effects in some populations and a restriction of range within test scores. We created a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…First, there are observed practice effects when the DOT is administered on back-to-back days (Momen, 2009). Second, there are a limited number of trials and a ceiling effect found within the aviator community (Keiser, et al, 2019). Last, recent assessments have shown that the DOT and updated versions of the DOT may not assess SpA as the task was intended (Coyne, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…First, there are observed practice effects when the DOT is administered on back-to-back days (Momen, 2009). Second, there are a limited number of trials and a ceiling effect found within the aviator community (Keiser, et al, 2019). Last, recent assessments have shown that the DOT and updated versions of the DOT may not assess SpA as the task was intended (Coyne, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The DOT 2 task was created as a potential alternative to address some of these short comings of the DOT (Keiser et al, 2019). Specifically, the DOT 2 has 144 possible trials, and reduces the chances of correctly guessing.…”
Section: Introductionmentioning
confidence: 99%
“…Understand an object's spatial orientating from an aerial view is clearly an important ability for pilots and the test certainly has face validity. However, there are limitations to this task, including a limited number of potential trials and a ceiling effect (Keiser et al, 2019). There is also evidence of a practice effect on the DOT, as accuracy and response time both improve on the task after exposure on consecutive days (Momen, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations